A Stakeholder Framework for Analyzing and Evaluating Corporate Social Performance - Clarkson, Max (Academy of Management Review, 1995)
This article presents conclusions from a 10-year research program, the purpose of which has been to develop a framework and methodology, grounded in the reality of corporate behavior, for analyzing and evaluating corporate social performance. There are three principal sections: (a) a summary of the approaches, models, and methodologies used in conducting more than 70 field studies of corporate social performance from 1983-1993; (b) a discussion of the principal conclusions derived from the data that (1) corporations manage relationships with stakeholder groups rather than with society as a whole, (2) it is important to distinguish between social issues and stakeholder issues, and (3) it is necessary to identify the appropriate level of analysis in order to evaluate CSP; and (c) a discussion of propositions and areas for further research.